Electronic Adherence Monitoring May Facilitate Intentional HIV Status Disclosure Among People Living with HIV in Rural Southwestern Uganda - Musiimenta, Angella; Campbell, Jeffrey I.; Tumuhimbise, Wilson; Burns, Bridget; Atukunda, Esther Cathyln; Eyal, Nir; Haberer, Jessica E. (AIDS and Behavior, 2021)
HIV status disclosure remains one of the major challenges to effective HIV prevention. Given the complexities and low rates of disclosure, new innovative strategies are needed. Since electronic adherence monitoring (EAM) are unique mobile devices that light up when transmitting data, those who see them often want to know more about them, which can potentially result in HIV status disclosure. We conducted a qualitative study to explore patient experiences with EAM for antiretroviral therapy (ART) in Uganda with a goal of understanding potential ethical concerns, including disclosure. Unexpectedly, several participants reported intentionally using EAM to facilitate HIV status disclosure to others in order to get social support, encourage HIV testing, and create awareness about HIV. Although researchers and clinicians need to be mindful of the potential for unintended HIV status disclosure through the use of EAM, they should also recognize the potential of this approach to support intended disclosure.
Keywords: HIV intentional disclosure; Electronic; Adherence; Uganda